Wavelet based Fault Detection Method for Ungrounded Power System with Balanced and Unbalanced load - Vishwakumar Revanasiddappa Sheelavant; Vijaya C; S C Shiralashetti (International Journal of Electrical and Computer Engineering (IJECE), 2011)
Modern spectral and harmonic analysis is based on Fourier transforms. However, these techniques are less efficient in tracking the signal dynamics for transient disturbances. Consequently, the wavelet transform has been introduced as an adaptable technique for non-stationary signal analysis. Although the application of wavelets in the area of power system engineering is still relatively new, it is evolving very rapidly. In this paper wavelet based method for detection of faults in an ungrounded integrated power system (IPS) of Navy ships is proposed. However the “Virtual ground” exists between the modules of IPS and ship hull, because of insulation capacitance of the cable and the EMI filters between the modules of the IPS. The fault current is very low for a single line to ground fault in this ungrounded system allowing continuous operation but also making fault detection difficult. The proposed method uses wavelets for detection of ground fault in ungrounded power system. The ground fault conditions are simulated using MATLAB-SIMULINK and fault detection implemented with Daubechies wavelets. It is shown that transient ground faults can be detected by wavelet analysis of the line to line voltages when ship load is balanced and unbalanced. Verification of the proposed method has been done by simulating fault between a line and ship hull and analyzing the results.DOI:http://dx.doi.org/10.11591/ijece.v1i1.57